THE EFFECT OF AEROB AND ANAEROBIC CONDITION AND ADDITION OF CaCO3 ON THE GROWTH AND ANTIBACTERIAL ACTIVITY OF LACTIC ACID BACTERIA ISOLATED FROM LAYER HENS INTESTINE AFTER ADMINISTRATED OF AKBISprob - Nurliana, Nurliana; Khairunisa, Fauzia; Musni, Nailah; Vanda, Henni; Rasmaidar, Rasmaidar; Hasan, Muhammad; Asmilia, Nuzul; Sari, Wahyu Eka; Isa, Muhammad (Jurnal Kedokteran Hewan, 2023)
This study aimed to determine the effect of aerobic and anaerobic incubation, and the addition of CaCO on the growth and antibacterial activity of Lactic Acid Bacteria (LAB) isolated from laying hens intestines (strain ISA Brown) after given 4% AKBISprob. The LAB used in this study was the isolates strains that produced the strongest antibacterial activity with inhibition zone 5 mm. The treatments consisted of two incubations condition (aerobic and anaerobic) with five concentrations of CaCO3 (1%, 2%, 3%, 4%, and 5%). Each treatment consisted of three repetitions. Total Plate Count (TPC) method and the agar diffusion method were used to calculate the amount of LAB and antibacterial activity, respectively. The results showed that anaerobic conditions had a significant effect (P0.05) on the increase of LAB growth, but both of aerobic and anaerobic conditions (P0.05) did not show significant effect on antibacterial activity. The addition of CaCO3 had a significant effect (P0.05) on the increase in growth and antibacterial activity of LAB. Based on the results of the study, it can be concluded that anaerobic incubation can increase the growth of two isolate of LAB isolates (P31S72 and P31H62), however aerobic and anaerobic incubation have no effect on antibacterial activity. In addition, the administration of 3% CaCO3 can increase the growth and antibacterial activity of all LAB isolates.